Ustādh-i bashar : Pizhūhishhāʾī dar zindagī, rūzgār, falsafah wa ʿilm-i Khwājah Naṣīr al-Dīn-i Ṭūsī (Wīzha nāmah Khājah Naṣīr al-Dīn-i Ṭūsī) - Ṭūsī, Naṣīr al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, he is especially known for such treatises as his Tajrīd al-iʿtiqād on theology; his Zīj-i Īlkhānī on astronomy; his commentary on Avicenna's (428/1037) Kitāb al-ishārāt wal-tanbīhāt on philosophy and logic; his Āghāz wa anjām on Ismaili eschatology; his Awṣaf-al-ashrāf on mysticism; and his Akhlāq-i Nāṣirī on ethics. In Iran Ṭūsī stands in high regard and studies on him abound. The present collection of articles was compiled with the aim of bringing a number of major publications by foreign and Iranian scholars within easy reach of the Persian reader. All the branches of Ṭūsī studies are represented: his life, times, and works, as well as his views and achievements in philosophy, theology, mysticism, and science.